2019
DOI: 10.2147/dmso.s205198
|View full text |Cite
|
Sign up to set email alerts
|

<p>Sex disparities in the epidemic of type 2 diabetes in Mexico: national and state level results based on the Global Burden of Disease Study, 1990–2017</p>

Abstract: Purpose: To analyze the type 2 diabetes (T2D) health burden in Mexico by sex at the national and state levels from 1990 to 2017. Methods: This was a secondary analysis based on data from the Global Burden of Disease Study, 1990-2017. We used the indicators of mortality rates, years of life lost due to premature mortality (YLLs), years lived with disability (YLDs), and disability-adjusted life years (DALYs). Results: At the national level, there was an increase in the standardized mortality rates, YLLs, YLDs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
1
9
0
2
Order By: Relevance
“…This coincides with the fact that mortality due to T2D in people aged 15 years or older in Mexico has increased by around 50% for men and 10% in women between 1990 and 2017. 32 The data also indicate that Mexican men receive less information regarding this disease than women, in addition to that, in general, people with T2D do not take controls to avoid or delay their complications, such as physical activity or modify the diet. 33 The differences by sex have been under-analysed, and little is known about the role that gender has regarding the progression and outcome of the various chronic diseases, 8 29 31 therefore, it is necessary that future research explores this subject in depth.…”
Section: Discussionmentioning
confidence: 95%
“…This coincides with the fact that mortality due to T2D in people aged 15 years or older in Mexico has increased by around 50% for men and 10% in women between 1990 and 2017. 32 The data also indicate that Mexican men receive less information regarding this disease than women, in addition to that, in general, people with T2D do not take controls to avoid or delay their complications, such as physical activity or modify the diet. 33 The differences by sex have been under-analysed, and little is known about the role that gender has regarding the progression and outcome of the various chronic diseases, 8 29 31 therefore, it is necessary that future research explores this subject in depth.…”
Section: Discussionmentioning
confidence: 95%
“…T2DM is the result of combined effects of genetic background, gender, aging, lifestyle, obesity and other factors [21]. Age and gender differences in risk, onset and progress of T2DM was found in previous studies [22,23]. Strati ed by gender and age, rs3825199, rs11107116 and rs10492321 conferred to the increased T2DM risk among males not females, and among the subjects aged at ≤ 60 years.…”
Section: Discussionmentioning
confidence: 83%
“… 6 , 7 , 26 Age and gender differences in the risk, onset, and progress of T2DM were found in previous studies. 27 , 28 When stratified by gender and age, rs3825199, rs11107116, and rs10492321 were conferred to an increased T2DM risk among males, and among the subjects aged ≤60 years ( Suppl_Table 3 ). Haplotype analysis revealed that GTA and AGT haplotypes had the higher T2DM susceptibility among males ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%